Optical Properties of Injection-Molded Polystyrene Scintillators. I. Processing and Optical Properties - Martins, J. A. (2003)
Scintillating tiles for the Tilecal/Atlas calorimeter can be produced by injection molding, an alternative to mold casting via in situ polymerization. This new production method, which leads to a much faster production rate, introduces a number of additional variables that affect the optical yield of the scintillators and that have not yet been reported in the literature. In this work, the effect of processing-induced orientation on the optical properties of the scintillators is analyzed and discussed. For this purpose, the birefringence across the thickness of the scintillator has been measured. The variations of the birefringence may be correlated with the orientation and, therefore, related to the optical performance, that is, the average light output and its nonuniformity.